LIGAND-BASED ANALYSIS OF COMPOUNDS ON GARLIC USING SWISS SIMILARITY - Reynaldi, Muhammad Andre (Universitas Tanjungpura, 2025)
Garlic (Allium sativum) is widely recognized for its bioactive compounds with potential therapeutic effects. This study aimed to conduct a ligand-based analysis of active garlic compounds using SwissSimilarity to identify structural similarities with known bioactive molecules. The compounds analyzed included allicin, alliin, and diallyl sulfide. Molecular structures were obtained from the PubChem database and analyzed through SwissSimilarity by selecting the